Evaluation of Pyrethroid Susceptibility in Culex pipiens of Northern Izmir Province, Turkey - Onur Guntay; Mehmet Salih Yikilmaz; Huseyin Ozaydin; Savas Izzetoglu; Asli Suner (Tehran University of Medical Sciences, 2018)
Background: Mosquitoes, being a nuisance species, are considered as one of the most important species in public health control programs due to their role as a vector in mosquito-borne diseases observed in humans and animals. We evaluated the susceptibility status of Culex pipiens collected from northern Izmir, Turkey in 2011-16. Methods: Mosquito larvae, collected from three different locations in northern İzmir, were reared in the laboratory. Adult susceptibility bioassays were performed using the WHO insecticide-impregnated papers including deltamethrin 0.05%, permethrin 0.75%, α-cypermethrin 0.05% and cyfluthrin 0.15%. In addition, adult bioassays were performed after the pre-exposure to piperonyl butoxide (PBO) to determine the contribution of P450 detoxification enzymes to the phenotypic resistance. Results: In all of the three populations, high levels of resistance were observed (mortalities<63%) to all of the four pyrethroids. Different pyrethroids but with the same mode of action can exhibit significantly different phenotypic resistance in a single population. PBO bioassays also showed that P450 detoxification enzymes can have diverse effects on different pyrethroids. Conclusion: Using just one chemical in a class of insecticide can be misleading for resistance studies.